2017
DOI: 10.1002/jctb.5447
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Candida antarctica lipase B in pressurized fluids for the synthesis of esters

Abstract: BACKGROUND The objective of this work was to evaluate the activation of Candida antarctica lipase B (CALB) in pressurized CO2 or liquefied petroleum gas (LPG) and, thereafter, to evaluate the synthesis of esters using activated CALB as a biocatalyst. Before activation, CALB was immobilized in polyurethane. For the esterification reactions, mechanical or ultrasonic agitations were studied. The stability of CALB after reuse cycles was also evaluated. RESULTS Before activation, the enzymatic activity of immobiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…Higher temperatures can reduce the viscosity of liquid media, as those studied in this work, thus reducing mass transfer resistances. Similar results were observed for the synthesis of different esters, such as hexyl levulinate (Badgujar & Bhanage, ) and ethyl oleate (Nyari et al, ). Furthermore, other similar results are reported on the acylation of rutin with lauric acid using CALB and Thermomyces lanuginosus lipases immobilized on different supports as catalysts (Razak & Annuar, ).…”
Section: Resultssupporting
confidence: 78%
“…Higher temperatures can reduce the viscosity of liquid media, as those studied in this work, thus reducing mass transfer resistances. Similar results were observed for the synthesis of different esters, such as hexyl levulinate (Badgujar & Bhanage, ) and ethyl oleate (Nyari et al, ). Furthermore, other similar results are reported on the acylation of rutin with lauric acid using CALB and Thermomyces lanuginosus lipases immobilized on different supports as catalysts (Razak & Annuar, ).…”
Section: Resultssupporting
confidence: 78%
“…Compared with free enzyme, immobilized enzyme presents several advantages: first, immobilized enzyme can be easily fixed on the surface of carriers of various shapes such as granular, tubular, and membranous, which is easy to remove and facilitates continuous and repeated use. Moreover, improved tolerance to environment conditions can be observed after immobilization, resulting in enhanced stability and longer working cycle for immobilized enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Adewale et al(2016) remarked that the reaction time was significantly reduced by ultrasound compared with traditional method; 96.8% yield was achieved within 20 min. In addition, the application of supercritical CO2 in enzymatic transesterification of waste animal fats to biodiesel is also a promising method to enhance enzyme activity and reaction rate by increasing the mass transfer rate and further reducing the toxicity of methanol to the enzyme(Lee et al, 2017;Nyari et al, 2018) Nyari et al (2018). demonstrated that the enzymatic activity of immobilized Candida antarctica lipase B increased from 189 U/g to 2486 U/g after activation in pressurized CO2,…”
mentioning
confidence: 99%